Use of perches and seed dispersal by birds in an abandoned pasture in the Porto Ferreira state park, southeastern Brazil - Athiê,S. (2016)
Abstract We investigated the efficiency of different kinds of perches in attracting seed disperser-birds and increasing the seed rain in a degraded area located in the northeast region of São Paulo State. We installed seed traps under natural perches (NPs, living trees); simple artificial perches (SAPs) of 3m tall and a crossbar; elaborate artificial perches (EAPs) of 7m tall and three crossbars, and in a control area. Results showed the number of bird-dispersed seeds deposited was proportional to the number of structures for perching. The NPs also have provided other resources for birds such as food and shelter. Comparing visitation between artificial perches, there was greater use of EAPs also for having more perching structures and for being taller, providing better airspace visibility for predatory birds and tyrant-flycatchers, important seed dispersers. Thus, natural and artificial perches with similar characteristics to the EAPs are the most recommended as a base or complementary method for the restoration of degraded areas near to propagules source, also contributing to the maintenance of local fauna.